Challenges and Strategies of Social Organizations' Participation in Community Public Affairs Management from the Perspective of Collaborative Governance - Yang, Fanduozi (International Journal of Humanities and Social Science, 2025)
The transformation of community governance in contemporary society has brought social organizations to the forefront of public affairs management. Under the framework of collaborative governance, the effective participation of these organizations is essential for achieving multi-actor coordination and improving community service delivery. However, their involvement is often constrained by institutional, resource, and capacity-related barriers. This paper analyzes the challenges faced by social organizations in participating in community public affairs from a collaborative governance perspective. It identifies five key problem areas: insufficient institutional support, fragmented resource allocation, limited organizational capability, weak trust and communication mechanisms, and coordination inefficiency among stakeholders. To address these issues, the paper proposes strategies including institutional synergy, resource integration, capacity enhancement, trust-building mechanisms, and digital empowerment. The study argues that fostering a sustainable collaborative system among government, social organizations, and community actors is vital for advancing participatory and effective community governance.